Vehicle automatic navigator data line connector - HE FUQIAN (2016)
The utility model provides a vehicle automatic navigator data line connector, including gluing the core, pintle hook lock and a plurality of terminal, glue and adjacently about the core rear end to be provided with two rows of guiding holes, every row of guiding hole including 5 next -door neighbours, dislocation set between the upper and lower guiding hole, inner wall in the middle of two rows of upper and lower guiding holes is opened has the trip bayonet socket, glue core top surface and bottom surface and all opened the pintle hook lock locating hole, the terminal simultaneously is provided with the draw -in groove, the draw -in groove back is provided with the shell fragment trip, be provided with the reference column that is used for blocking terminal card slot on the pintle hook lock, the terminal passes through the guiding hole and gets into gluey in -core, shell fragment trip card advances the trip bayonet socket in the guiding hole, the draw -in groove is just to the pintle hook lock locating hole,